The physiology of the world record holder for the women`s marathon - Jones, A. M. (International Journal of Sports Science and Coaching, 2006)
The purpose of this paper is to review the physiological determinants of endurance exercise performance by using the data of the World Record holder for the women`s marathon (PR), to illustrate the link between an athlete`s physiology and success in distance running. The maximal xygen (O2) uptake, O2 cost of running at sub-maximal speeds (running economy), and blood lactate response to exercise can all be determined using standard physiology laboratory exercise tests and the results used to track changes in `fitness` and to make recommendations for future training. PR`s data demonstrate a 15% improvement in running economy between 1992 and 2003 suggesting that improvements in this parameter are very important in allowing a distance runner to continue to improve their performance over the longer-term. PR`s data demonstrate how 15 years of directed training have created the`complete` female distance runner and enabled the setting of an extraordinary World record of 2:15:25 for the Marathon.